2010
DOI: 10.4067/s0718-19572010000200009
|View full text |Cite
|
Sign up to set email alerts
|

El parasitismo por Profilicollis bullocki (Acanthocephala: Polymorphidae) en Emerita analoga (Anomura: Hippidae) según condiciones contrastantes de abundancia de hospedadores definitivos en Chile

Abstract: In Chile, the intermediate host of the acanthocephalan Profilicollis bullocki is the mole crab Emerita analoga, with seabirds as the definitive hosts, who arrive in mass during summer, enhancing the spread of acanthocephalan eggs to the environment. Thus, the magnitude of this parasitosis in E. analoga should attain higher values after the yearly arrival of seabirds. This study was performed in two periods contrasting in the abundance of marine birds, September-November 2008 (late winter-spring) and December 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
3
0
2
Order By: Relevance
“…The life cycles of almost all acanthocephalan and digenetic species, as well as some nematodes and cestodes, include at least one intermediate host that accumulates parasites over time ( Thomas, Guégan & Renaud, 2009 ). In addition, size-dependent responses of prevalence to parasite exposure have been demonstrated in other complex host-parasite interactions involving migratory birds and crustaceans ( Latham & Poulin, 2003 ; Smith, 2007 ; Zambrano & George-Nascimento, 2010 ). In the same line, parasite burden increases with body size of the toadfish Aphos porosus Valenciennes, 1837, an intermediate host of cestodes, nematodes, trematodes, and acantocephalans ( Cortés & Muñoz, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The life cycles of almost all acanthocephalan and digenetic species, as well as some nematodes and cestodes, include at least one intermediate host that accumulates parasites over time ( Thomas, Guégan & Renaud, 2009 ). In addition, size-dependent responses of prevalence to parasite exposure have been demonstrated in other complex host-parasite interactions involving migratory birds and crustaceans ( Latham & Poulin, 2003 ; Smith, 2007 ; Zambrano & George-Nascimento, 2010 ). In the same line, parasite burden increases with body size of the toadfish Aphos porosus Valenciennes, 1837, an intermediate host of cestodes, nematodes, trematodes, and acantocephalans ( Cortés & Muñoz, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…We observed that molecrab recruitment strongly varied across geographic locations, with site-dependent peaks occurring in summer, autumn, and spring (but see Contreras, Defeo & Jaramillo, 1999 ). An increase in non-infected recruits can have negative (positive) effects on prevalence (aggregation) across the host population (e.g., Zambrano & George-Nascimento, 2010 ), which might decouple the relationship between exposure and the parasitosis in the intermediate host. Further field-based comparative experiments would be useful to tease apart the effects of exposure, egg mortality, and recruitment timing on parasite aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the host related environmental work pertaining to this species, was, however, reported from Pacific South America. In Chile, sea birds arriving in mass numbers during the summer enhance the spread of acanthocephalan eggs to the environment, producing higher values of infection in E. analoga [ 58 , 80 ]. The identity of definitive host species was found to be relevant to morphometric and reproductive variations (fecundity) of P. altmani with acanthocephalans of 2 species of Larus attaining larger body size than those in 2 other genera of gulls from the Chilean coast [ 56 ].…”
Section: Introductionmentioning
confidence: 99%
“…Esto demuestra que altas cargas de parásitos en sus hospedadores intermediarios no implica que estén en lugares con altas abundancias de hospedadores definitivos, especialmente al relacionarlos con hospedadores secundarios (e.g., digéneos en crustáceos). Existen algunos estudios, que han encontrado relaciones significativas entre la abundancia de hospedadores definitivos y la prevalencia o abundancia de parásitos en hospedadores intermediarios (e.g., Fredensborg et al, 2006;Zambrano & George-Nascimento, 2010), pero esto depende del ciclo de vida de los parásitos y de su transmisión. Por ejemplo, las aves que tienen digeneos adultos pueden liberar los huevos del parásito en las heces, en zonas intermareales donde se encuentran los hospedadores intermediarios, es decir gasterópodos que son directamente infectados con larvas miracidios de digeneos que eclosionan de los huevos.…”
Section: Discussionunclassified
“…En el ambiente marino, los crustáceos son depredados por un vertebrado (pez, ave o mamífero) donde el endoparásito se desarrolla hasta alcanzar el estado adulto (Rohde, 2005). Sin embargo, a pesar de la importancia que cumplen los crustáceos en el ciclo de vida de endoparásitos marinos, en Chile son muy pocos los estudios parasitológicos realizados en crustáceos decápodos (Muñoz & Olmos, 2008;Oliva et al, 2008;Saldanha et al, 2009;Zambrano & George-Nascimento, 2010), sobre todo en aquellos que habitan en pozas del intermareal rocoso, pese a la alta abundancia que tienen en este ambiente.…”
Section: Introductionunclassified